Rey Auditory Verbal Learning Test and Rey–Osterrieth Complex Figure Test performance validity indices in a VA Polytrauma sample. Issue 8 (17th November 2019) - Ashendorf, Lee
Abstract: Objective: Performance validity assessment is a crucial component of any neuropsychological evaluation, particularly in settings where potential exaggeration of complaints and deficits is heightened. Standalone performance validity measures can be time-consuming, so many investigations have explored embedded indices within existing measures. The Rey Auditory Verbal Learning Test (RAVLT) and the Rey–Osterrieth Complex Figure Test (ROCF) each have a number of available embedded performance validity tests (PVTs). This investigation sought to evaluate several of these indices and to identify the most effective within a VA mild traumatic brain injury (mTBI)/Polytrauma sample. Method: A sample of 100 U.S. military veterans underwent clinical neuropsychological evaluation. There were 37 individuals whose test results were considered invalid based on failure of 2 or more independent PVTs, 47 whose results were valid, and 16 whose results were equivocal (failure on one PVT). The classification accuracies of published PVTs from the RAVLT and ROCF were evaluated. Results: Several indices had sensitivity values above 50% and strong positive predictive power with specificity held over 90%. Conclusions: The results demonstrated that there are multiple effective RAVLT & ROCF PVTs available for use in mTBI evaluations with veterans.